2016
DOI: 10.1111/jgh.13196
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Asia Pacific Colorectal Screening (APCS) score in a Western population: An alternative screening tool

Abstract: APCS predicts colonic findings in a Western population, to a greater extent than in Asians, independent to symptoms. Low body weight carries a strong protective effect against colonic neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Henceforth, The Asia-Pacific Working Group on CRC managed to identify important risk factors in Asian population and to derive a risk score tool which was named APCS score [10]. Subsequently, Thailand [16], Beijing [11,26], Japan [15], Hong Kong [12][13][14], South Korea [27], Vietnam [17], and Australia [28] all evaluated APCS score, which can be used as a cost-effective strategy in large asymptomatic cohort. In our study, the rate of ACRN in the asymptomatic group, LR, MR, and HR subgroups was 1.3, 8.6, and 20.3%.…”
Section: Discussionmentioning
confidence: 99%
“…Henceforth, The Asia-Pacific Working Group on CRC managed to identify important risk factors in Asian population and to derive a risk score tool which was named APCS score [10]. Subsequently, Thailand [16], Beijing [11,26], Japan [15], Hong Kong [12][13][14], South Korea [27], Vietnam [17], and Australia [28] all evaluated APCS score, which can be used as a cost-effective strategy in large asymptomatic cohort. In our study, the rate of ACRN in the asymptomatic group, LR, MR, and HR subgroups was 1.3, 8.6, and 20.3%.…”
Section: Discussionmentioning
confidence: 99%
“…They assessed the utility of the APCS system and the presence of MS components and found that in cases with obesity, the colorectal tumor detection rate significantly increased (59.5% vs 19.2% for the MR/HR group without obesity, P < 0.01). Utilization of the APCS scoring system in the Western population was examined in an Australian study by Corte et al[ 54 ]. APCS predicts the colonic findings in a Western population to a greater extent than in Asians, independent of the symptoms.…”
Section: Asia-pacific Colorectal Screening Scoring Systemmentioning
confidence: 99%
“…Later, the usefulness of the APCS score as a preditor for advanced neoplasia has been studied in different racial population including Chinese, 14 Korean, 15 Vietnamese, 16 Thais, 17 and Western population. 18 An evidence based on the use of risk score (APCS score) combining with FIT to prioritize subjects for colonoscopy and to reduce colonoscopy workload is emerging. A previous study from Thailand evaluated the combination of the APCS score and FIT to predict advanced neoplasia and to prioritize colonoscopy.…”
Section: Introductionmentioning
confidence: 99%